English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Square root of (x-1)^2 = the square root of 3

2007-01-18 12:42:44 · 5 answers · asked by cowboysblow27 3 in Science & Mathematics Mathematics

5 answers

((x-1)^2)^(1/2) = 3^(1/2)
x-1 = 3^(1/2)
x = 1+ 3^(1/2)

When you take the square root of a perfect square, you get the root.

2007-01-18 12:51:46 · answer #1 · answered by Brian F 4 · 0 0

Square root of (x-1)^2 = the square root of 3
sqrt(A) = sqrt(B) <=> A = B and A >= 0 or B >=0
thus
<=> (x-1)^2 = 3
<=> x^2 -2x - 2 =0
<=> x = 1 + sqrt(3) or x = 1 - sqrt(3)

2007-01-18 21:33:20 · answer #2 · answered by James Chan 4 · 0 0

Clear the square root from both sides. Presuming that the entire expression (x-1)^2 is under the root sign, your equation becomes:

(x-1)^2 = 3

then

x^2-2x+1 = 3
x^2-2x-2 = 0

Use the quadratic equation to solve, which should give you two solutions: 1 + (sq.rt.12)/2 and 1 - (sq.rt. 12)/2

2007-01-18 20:54:15 · answer #3 · answered by TheOnlyBeldin 7 · 0 0

sqrt[(x-1)^2] = sqrt[3]

the square root of a squared value is simply the value itself, so:
(x-1) = sqrt[3]

which means:
x = sqrt[3] + 1

x= 1.732 + 1

therefore:
x = 2.732

2007-01-18 20:55:49 · answer #4 · answered by thubanconsulting 3 · 0 0

wHAT DOES ^ 2 MEAN?

2007-01-18 20:48:37 · answer #5 · answered by Sarah 1 · 0 0

fedest.com, questions and answers